Video-Based Ergonomic Assessment for Spacesuit Training in a Microgravity Analog. (November 2019) - Hernandez, Yaritza; Han Kim, K.; Benson, Elizabeth; Jarvis, Sarah; Rajulu, Sudhakar
Astronauts are trained in a simulated reduced gravity environment at the NASA Johnson Space Center's Neutral Buoyancy Laboratory (NBL), an underwater test facility. While crewmembers and spacesuits may have a net effect of weightlessness in this environment, their own weight still forces them against the suit. With the extensive amount of required spacesuit training, an association has been observed between suit exposure time and astronaut injuries. The goal of this study was to identify possible relationships between spacesuit training and extreme underwater work postures that are related to injury risk. Given the limitation of traditional ergonomic evaluation tools because of the complex motion of the spacesuit in an underwater environment, a new tool was developed and tested to measure the three-dimensional orientation of suited test subjects in analysis of NBL training videos. A wireless motion tracking device was paired with an event logging software to quantitatively log the upper body orientations throughout training videos.